2019
DOI: 10.1590/1983-21252019v32n101rc
|View full text |Cite
|
Sign up to set email alerts
|

Weeds as Potential Hosts for Fungal Root Pathogens of Watermelon

Abstract: Many watermelon (Citrullus lanatus) diseases are caused by soilborne pathogens in Brazil and worldwide. The goal of this study was to identify and quantify the frequency of phytopathogenic fungi associated with watermelon root rot and vine decline that were also present in the roots of weeds in the major watermelon production regions in the state of Rio Grande do Norte, Brazil. We collected root samples from 10 of the most prevalent weed species in 16 watermelon producing areas. The plants were identified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, there is still no specific report mentioning the amount of dropped results caused by weed competition with the cultivated crops. The presence of weed in the horticultural land can indirectly be the alternative host for some pathogens, namely bacteria, fungi, viruses, and nematode (Sales Júnior et al, 2019). A. conyzoides can be an alternative host for Begomovirus (Leke et al, 2012).…”
Section: Results and Discussion Nematode Infection Symptoms On Weedsmentioning
confidence: 99%
“…Nevertheless, there is still no specific report mentioning the amount of dropped results caused by weed competition with the cultivated crops. The presence of weed in the horticultural land can indirectly be the alternative host for some pathogens, namely bacteria, fungi, viruses, and nematode (Sales Júnior et al, 2019). A. conyzoides can be an alternative host for Begomovirus (Leke et al, 2012).…”
Section: Results and Discussion Nematode Infection Symptoms On Weedsmentioning
confidence: 99%
“…This is the first molecular diagnosis of M. phaseolina associated with watermelon in Northeastern Brazil. Negreiros et al (2019) andSales Júnior et al (2019a) reported the pathogen associated with weeds infesting melon and watermelon production fields in the region. In watermelon, charcoal rot caused by M. phaseolina occurs at the end of the crop cycle and symptoms are directly influenced by the infestation level in the growing areas (Cohen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cropping and expansion of planted areas without effective disease management increased the incidence and severity of numerous pathologies in producing fields in the Northeast region (SALES JÚNIOR et al, 2019). Root rot and vine declining (RRVD), caused by soilborne fungi species, limits melon production in the region (PORTO et al, 2019;SALES JÚNIOR et al, 2012).…”
Section: Introductionmentioning
confidence: 99%